Accurate Software Implementation For Accounting Information System Corporate (Case Study Yanata) - Ong Felycia Christiana; Rinabi Tanamal; Kartika Gianina Tileng (Jurnal Manajemen dan Bisnis Indonesia, 2015)
Financial bookkeeping is the most important thing in any company. Bookkeeping manually using books and calculator, often make a lot of mistakes in calculations and accuracy. Digital bookkeeping make easier for companies to store data and evidence for each record that will be used in the books of each company. "Yanata" is a AC distributor company (Air Conditioner) that located in Surabaya. Mrs. Ribkah Soerjani as the owner of "Yanata" has some problems that add jobs and spend more time. One problem is the problem of accounting "Yanata". To obtain accurate data is not very easy. The purpose of the author to make final project is to provide solutions to design the flow of information systems to provide and teach accounting software for "Yanata". By interviewing the owner of "Yanata" to find out what are the needs for company, the author can implement Accurate software. At the end of the implementation, the author hope that the Accurate software has answered what "Yanata" needs. Keywords: company, software, Accurate, accounting, training